System approach of organization methods and ways of road construction mobilization of permanent and temporary roads at construction sites - Oleynik, Pavel; Kazaryan, Ruben; Doroshin, Ivan; Avetisyan, Robert (Edelweiss Applied Science and Technology, 2024)
Today, the issue of a qualitative approach to the design and construction of temporary roads at a construction site is particularly important for the organization of construction. For the construction of temporary roads and their effective functioning, it is very important to achieve high performance characteristics of the road surface. The article discusses the road surface Imprint – a new technological solution for the construction of temporary roads. Objective: The purpose of the study is to determine the possibility of using this coating as a coating for temporary and permanent roads. Results: The results of the study showed that Imprint coatings can be successfully applied where there is heavy traffic. Conclusion: The schedule of work is one of the main documents of the programme of work. It reflects the decision on the organization of work, the chosen organization method and the way of its mobilization, the sequence of technological processes, the arrangement of equipment and workers in private flows, contains other production and technical information. Imprint road surfaces have sufficient strength, have good abrasion resistance, impact strength, does not slip under the wheels of cars and pedestrians’ feet, is resistant to the formation of ruts, resists aggressive environments well, has improved hygienic indicators. It is recommended to use Imprint road surfaces on a construction site.